Emergence of Marburg virus: a global perspective on fatal outbreaks and clinical challenges - Srivastava, Shriyansh; Sharma, Deepika; Kumar, Sachin; Sharma, Aditya; Rijal, Rishikesh; Asija, Ankush; Adhikari, Suraj; Rustagi, Sarvesh; Sah, Sanjit; Al-qaim, Zahraa Haleem; Bashyal, Prashant; Mohanty, Aroop; et al. (Frontiers in Microbiology, 2023)
The Marburg virus (MV), identified in 1967, has caused deadly outbreaks worldwide, the mortality rate of Marburg virus disease (MVD) varies depending on the outbreak and virus strain, but the average case fatality rate is around 50%. However, case fatality rates have varied from 24% to 88% in past outbreaks depending on virus strain and case management. Designated a priority pathogen by the National Institute of Allergy and Infectious Diseases (NIAID), MV induces hemorrhagic fever, organ failure, and coagulation issues in both humans and non-human primates. This review presents an extensive exploration of MVD outbreak evolution, virus structure, and genome, as well as the sources and transmission routes of MV, including human-to-human spread and involvement of natural hosts such as the Egyptian fruit bat (Rousettus aegyptiacus) and other Chiroptera species. The disease progression involves early viral replication impacting immune cells like monocytes, macrophages, and dendritic cells, followed by damage to the spleen, liver, and secondary lymphoid organs. Subsequent spread occurs to hepatocytes, endothelial cells, fibroblasts, and epithelial cells.MV can evade host immune response by inhibiting interferon type I (IFN-1) synthesis. This comprehensive investigation aims to enhance understanding of pathophysiology, cellular tropism, and injury sites in the host, aiding insights into MVD causes. Clinical data and treatments are discussed, albeit current methods to halt MVD outbreaks remain elusive. By elucidating MV infection's history and mechanisms, this review seeks to advance MV disease treatment, drug development, and vaccine creation. The World Health Organization (WHO) considers MV a highconcern filovirus causing severe and fatal hemorrhagic fever, with a death rate ranging from 24% to 88%. The virus often spreads through contact with infected individuals, originating from animals.Visitors to bat habitats like caves or mines face higher risk. We tailored this search strategy for four databases: Scopus, Web of Science, Google Scholar, and PubMed. we primarily utilized search terms such as "Marburg virus," "Epidemiology," "Vaccine," "Outbreak," and "Transmission." To enhance comprehension of the virus and associated disease, this summary offers a comprehensive overview of MV outbreaks, pathophysiology, and management strategies. Continued research and learning hold promise for preventing and controlling future MVD outbreaks.